Keterkaitan Hukum Pajak dan Hukum Perdata dalam Menentukan Objek Pajak atas Transaksi Sipil - Alya Dwi Ananta (Mahalini: Journal of Business Law, 2025)
The rapid development of digital technology has brought significant changes to the music industry, particularly in the mechanisms of distributing and monetizing artists' works. Digital distribution platforms like Believe.com play a crucial role in connecting musicians with the global market through distribution, promotion, and royalty management services. However, the protection of musicians' royalties in the digital era still faces various challenges, such as unequal revenue sharing and the risk of piracy. This research discusses the royalty protection mechanisms implemented by Believe.com, including its royalty management and transparency systems, and their impact on the sustainability of musicians' careers in the digital realm. This research also examines how Believe.com contributes to creating a fair and inclusive ecosystem for both independent musicians and major labels amidst the dynamics of the digital music industry. Findings indicate that innovation in digital distribution and royalty management is essential to ensure copyright protection and improve the welfare of musicians in the digital era, in line with the principles stipulated in Law Number 28 of 2014 concerning Copyright.